On the problem of possible last-glacial forest-refuge-areas within the deep valleys of eastern Tibet - Frenzel, Burkhard; Bräuning, Achim; Adamczyk, Sonja (ERDKUNDE, 2003)
Based on the results of our six expeditions to the Tibetan Plateau, it was investigated, whether, during the last glaciation forest refuge-areas had only existed at the periphery of the Tibetan Plateau, as it is generally suggested, or within the deep East-Tibetan river gorges, as well. This investigation was done by pollen analyses on peat-bogs, which date from the Late-glacial to Holocene transition or at least from the very beginning of the Holocene, and by dendroclimatological studies and studies on the distribution pattern of various botanical taxa with the support of international literature. The following results were obtained: 1) All three methodical approaches equivocally point to forest-refuge areas in the region of the deep East-Tibetan river gorges, which seem to have existed during the last glaciation. 2) It is unknown, whether one or more of these refuge-areas existed. 3) The history of these refuge-areas still remains unknown.